Methodology for the Design and Evaluation of Self-Healing LTE Networks. - Gómez-Andrades, Ana; Muñoz, Pablo; Khatib, Emil Jatib; De la Bandera Cascales, Isabel; Serrano, Inmaculada; Barco-Moreno, Raquel (IEEE, 2015)
Self-healing networks aim to detect cells with service degradation, identify the fault cause of their problem, and execute compensation and repair actions. The development of this type of automatic system presents several challenges to be confronted. The first challenge is the scarce number of historically reported faults, which greatly complicates the evaluation of novel self-healing techniques. For this reason, in this paper, a system model to simulate faults in Long-Term Evolution (LTE) networks, along with their most significant key performance indicators, is proposed. Second, the expert knowledge required to build a self-healing system is usually not documented. Therefore, in this paper, a methodology to extract this information from a collection of reported cases is proposed. Finally, following the proposed methodology, an automatic fuzzy-logic-based system for fault identification in LTE networks is designed. Evaluation results show that the fuzzy system provides fault identification with a high success rate.
https://v2.sherpa.ac.uk/id/publication/3582
Keywords: Sistemas de comunicaciones inalámbricos; LTE (Telecomunicaciones); Mobile communication; Mobile computing; Interference; Fault diagnosis; Design methodology; Antenna radiation patterns; Fuzzy logic; Root cause analysis; Troubleshooting